Finite element computation of the effective thermal conductivity of two-dimensional multi-scale heterogeneous media. Issue 5 (28th August 2018) - Mattos, Lucas Prado; Cruz, Manuel Ernani; Bravo-Castillero, Julián
Abstract : Purpose: The simulation of heat conduction inside a heterogeneous material with multiple spatial scales would require extremely fine and ill-conditioned meshes and, therefore, the success of such a numerical implementation would be very unlikely. This is the main reason why this paper aims to calculate an effective thermal conductivity for a multi-scale heterogeneous medium. Design/methodology/approach: The methodology integrates the theory of reiterated homogenization with the finite element method, leading to a renewed calculation algorithm. Findings: The effective thermal conductivity gain of the considered three-scale array relative to the two-scale array has been evaluated for several different values of the global volume fraction. For gains strictly above unity, the results indicate that there is an optimal local volume fraction for a maximum heat conduction gain. Research limitations/implications: The present approach is formally applicable within the asymptotic limits required by the theory of reiterated homogenization. Practical implications: It is expected that the present analytical-numerical methodology will be a useful tool to aid interpretation of the gain in effective thermal conductivity experimentally observed with some classes of heterogeneous multi-scale media. Originality/value: The novel aspect of this paper is the application of the integrated algorithm to calculate numerical bulk effective thermal conductivity values for multi-scale heterogeneous media.